Effects of local handwashing agents on microbial contamination of hands in the rural settings of northwest Ethiopia: protocol for a two-arm, clustered-randomised controlled trial - Bikes Destaw Bitew; Jiyoung Lee; Zemichael Gizaw; Alemayehu Worku Yalew; Michael Bisesi (BMJ Open)
Introduction Hands play a part in the transmission of infections. Handwashing with soap sufficiently reduces the level of hand contamination and the spread of infections. As soap is not usually available due to cost, ash is often used as a zero-cost alternative to soap in the rural settings of developing countries. However, there is limited evidence on the effectiveness of ash to reduce microbial contamination of hands. This study is, therefore, designed to assess the effect of ash on microbial contamination of hands in the rural settings of northwest Ethiopia.Methods and analysis A two-arm clustered-randomised controlled trial will be employed. A total of 11 clusters per arm will be selected using simple random sampling technique. A total of 220 mothers or caregivers of under-5 children will be included in each arm. After providing health education on effective handwashing process, we will ask study subjects to do the usual activities. We will then take swab samples from the dominant hand before washing. After swabbing, participants will be asked to wash their hands with water only and with ash by following effective handwashing procedures. We will again take swab samples from the dominant hand after washing and drying. Finally, we will compare each intervention arm against the control. A generalised estimating equation (GEE) with robust SE estimation will be used to account the cluster nature of data.Ethics and dissemination Results will be published in peer-reviewed journal and presented at international conferences. The protocol is approved by the Institutional Review Board of the University of Gondar, Ethiopia.Trial registration number Pan African Clinical Trial Registry; PACTR202011855730652.